Analysis of the Development of Regulations and Policies in the World of Table Tennis: A Literature Study Approach - Nasution, Usman; Nasution, Muhammad Alfa Himawan; Habibi, Muhammad Iqbal; Tahira, Wan Liska Aulina; Ridoh, Muhammad (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The world of sports, including the realm of table tennis, continues to undergo developments in regulations and policies governing various aspects of competition and sport development. This research aims to conduct an in-depth analysis of the evolution of regulations and policies in the world of table tennis through a literature study approach. Relevant sources of literature, including scholarly journals, books, documents from table tennis federations, and popular articles, are identified and systematically analyzed. The results of the analysis indicate significant changes in technical rules of competition and sport development policies, reflecting efforts to maintain the relevance and integrity of this sport in the face of evolving challenges and opportunities. Additionally, global factors such as technological advancements and trends in sports, as well as the political, economic, and social contexts in each country, also influence the formation and implementation of these changes. However, this research acknowledges limitations in the scope of analysis and the need for further research to deepen understanding of regulatory dynamics in table tennis. Thus, this study provides valuable contributions to the literature on regulations and policies in sports and lays a solid foundation for further research and policy development in the future.